#MirandaMustGo: Contesting a settler colonial obsession with lost-in-the-bush myths through public and socially engaged art. Issue 2 (1st December 2019) - Spiers, Amy
In January 2017, settler Australian artist, Amy Spiers, launched a creative campaign to contest habitual associations at the site of Hanging Rock in Central Victoria with a white vanishing myth. Entitled #MirandaMustGo, the campaign's objective was to provoke thought and unease about why the missing white schoolgirls of Joan Lindsay's fictional novel, Picnic at Hanging Rock, prompted more attention and feeling in the general public than the actual losses of lives, land and culture experienced by Indigenous people in the region as a consequence of rapid and violent colonial occupation. The campaign incited significant media attention, substantial public debate and some reconsideration of the stories told at Hanging Rock. In this article, Spiers will describe how she conceptualized the artwork/campaign as a propositional counter-memorial action that attempted to conceive ways in which non-Indigenous Australians can acknowledge, and take responsibility for, the denial of colonization's impact on Indigenous people. She will do so by discussing the critical methodology that underpinned this socially engaged artwork and continue by analysing the public reception and dissensus the campaign provoked. She will conclude in presenting some thoughts about what #MirandaMustGo produced: a rupture of the public secret of Australia's violent colonial past, a marked shift to the discourse concerning Hanging Rock and an ongoing, unresolved agitation stimulated by Picnic at Hanging Rock's persistent reproducibility.